Drowsiness Detection of Driver While Driving Using MatLab - Shyamprasad, Dave Ruchita (My University, 2014)
Various investigations show that driver’s drowsiness is one of the main causes of road accidents. The development of technologies for preventing drowsiness at the time is a major challenge in the field of accident avoidance. The advance in computing technology has provided the means for building intelligent vehicle systems. The purpose of this study is to detect the drowsiness in drivers to prevent the accidents and to improve the safety on the highways. A system aiming at detecting driver drowsiness or fatigue on the basis of video analysis is presented. A real time face detection is implemented to locate driver’s face region. A method of detecting drowsiness in drivers is developed by using a camera that points directly towards the driver’s face and capture for the video. As a detection method, the system uses image processing technology to analyze images of the driver’s face taken with a video camera. The captured video is done, it is converted into number of frames of images and monitoring of the face region and eyes in order to detect drowsiness. The system is able to monitoring eyes and determines whether the eyes are in an open or shows signs of drowsiness. This detection system provides a noncontact technique for judging various level of alertness and facilitates early detection of a decline in alertness during driving
ME-Dissertation
Keywords: Drowsiness detection ,Histogram,erosion